Poly(lactic acid)/ethylene vinyl acetate copolymer blend composites with wood flour and wollastonite: Physical properties, morphology, and biodegradability. Issue 4 (24th January 2019) - Chaiwutthinan, Phasawat; Chauyjuljit, Saowaroj; Thipkham, Nutthawut; Kowalski, Chatr Panithipongwut; Boonmahitthisud, Anyaporn
Abstract : In the present study, poly(lactic acid) (PLA), a biodegradable plastic, was melt‐blended with five weight percentages (10–50 wt%) of ethylene vinyl acetate (EVA) copolymer, a non‐biodegradable plastic, having a vinyl acetate content of 19 wt% and a melt flow index of 530 g/10 min, on a twin screw extruder, followed by an injection molding. The blends at 10 and 20 wt% EVA revealed a noticeably increased impact strength and strain at break over the pure PLA, and the blend at 10 wt% EVA exhibited the highest impact strength and strain at break. The 90/10 (wt%/wt%) PLA/EVA blend was then selected for preparing either single or hybrid composite with wood flour (WF) and wollastonite (WT). The filler loading was fixed at 30 parts by weight per hundred of resin throughout the experiment, and the WF/WT weight ratios were 30/0, 20/10, 15/15, 10/20, and 0/30. The prepared composites were examined for their mechanical and thermal properties, melt flow index, flammability, water uptake, and biodegradability as a function of composition. All the composites showed a filler‐dose‐dependent decrease in the impact strength and strain at break, but an increase in the tensile and flexural modulus (optimal at 0/30 WF/WT) and tensile and flexural strength (optimal at 30/0 WF/WT) as compared with the neat 90/10 (wt%/wt%) PLA/EVA blend. In addition, the melt flow index, char residue, anti‐dripping ability, water uptake, and biodegradability of the composites were also higher than those of the neat blend. J. VINYL ADDIT. TECHNOL., 25:313–327, 2019. © 2019 Society of Plastics Engineers